Students' Physical Health and Healthy Lifestyle - Manasova Izimkul Serdanovna (International Journal on Integrated Education, 2021)
This article analyzes the role of rational nutrition, physical culture, morning exercises and the influence of bad habits (Smoking, alcohol consumption). The article focuses on the attitude of students to health as a social value. The authors cite the results of a sociological study, which testify to the prevalence of a stereotypical opinion among the younger generation on a healthy lifestyle and health in the process of forming a healthy lifestyle for young people. Also, the article reveals the importance of morning hygienic gymnastics in the process of forming a correct lifestyle.a